MANAJEMEN PENDIDIKAN DALAM PERSPEKTIF ALQUR’AN - HASAN ZAINI (IAIN Batusangkar, 2016)
Management of education in perspective al-Qur’an. The Qur'an is the way of life of all time, which is relevant in every time, place and situation . In the Qur'an not only discussed the matter of belief, worship, morals, halal and haram , but there are also issues of science. Among them about education issues, including the scope of Management Education. Word